Genome-Wide Characterization of ISR Induced in Arabidopsis thaliana by Trichoderma hamatum T382 Against Botrytis cinerea Infection - Mathys, Janick; De Cremer, Kaat; Timmermans, Pieter; Van Kerkhove, Stefan; Lievens, Bart; Vanhaecke, Mieke; Cammue, Bruno; De Coninck, Barbara (Frontiers in Plant Science, 2012)
In this study, the molecular basis of the induced systemic resistance (ISR) in Arabidopsis thaliana by the biocontrol fungus Trichoderma hamatum T382 against the phytopathogen Botrytis cinerea B05-10 was unraveled by microarray analysis both before (ISR-prime) and after (ISR-boost) additional pathogen inoculation. The observed high numbers of differentially expressed genes allowed us to classify them according to the biological pathways in which they are involved. By focusing on pathways instead of genes, a holistic picture of the mechanisms underlying ISR emerged. In general, a close resemblance is observed between ISR-prime and systemic acquired resistance (SAR), the systemic defense response that is triggered in plants upon pathogen infection leading to increased resistance towards secondary infections. Treatment with Trichoderma hamatum T382 primes the plant (ISR-prime), resulting in an accelerated activation of the defense response against Botrytis cinerea during ISR-boost and a subsequent moderation of the Botrytis cinerea induced defense response (BIDR). Microarray results were confirmed for representative genes by qRT-PCR, by analysis of transgenic plants expressing relevant promoter-GUS constructs and by phenotypic analysis of mutants affected in various defense-related pathways, thereby proving the validity of our approach.